2005
DOI: 10.2460/ajvr.2005.66.1665
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled study of inhaled fluticasone propionate, oral administration of prednisone, and environmental management of horses with recurrent airway obstruction

Abstract: Environmental management is the most important factor in the treatment of horses with RAO. Early treatment with inhaled fluticasone can help accelerate recovery of horses with severe RAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 31 publications
3
60
1
3
Order By: Relevance
“…One study found that long‐term dexamethasone and fluticasone treatment did not reverse the airway neutrophilia when RAO horses are kept indoors and exposed to hay even after 6–7 months 6. Other studies showed an additive effect on clinical signs, airway neutrophilia, and inflammatory cytokines in RAO horses when combining corticosteroid treatment with measures to improve air quality 6, 115, 116…”
Section: Treatment For Iadmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that long‐term dexamethasone and fluticasone treatment did not reverse the airway neutrophilia when RAO horses are kept indoors and exposed to hay even after 6–7 months 6. Other studies showed an additive effect on clinical signs, airway neutrophilia, and inflammatory cytokines in RAO horses when combining corticosteroid treatment with measures to improve air quality 6, 115, 116…”
Section: Treatment For Iadmentioning
confidence: 99%
“…It is thought that the risks of developing adverse effects associated with this treatment might be increased compared to inhaled corticosteroids,118 although the evidence is weak. Inhaled beclomethasone and fluticasone can be administered by metered dose inhaler via specialized delivery devices 115, 119, 120, 121. However, a fluticasone propionate metabolite was observed in the blood and urine when the drug was administered by inhalation at therapeutic doses,122 and adrenal suppression was detected after administration of beclomethasone dipropionate by inhalation 118…”
Section: Treatment For Iadmentioning
confidence: 99%
“…These medications are administered by metered dose inhaler via specialized delivery devices and they have proven to be clinically effective in horses with RAO with diminished risk of systemic adverse effects. 51,52 Anecdotal evidence suggest that the same drugs are beneficial for the treatment of IAD and dosages are usually lower that for RAO therapy.…”
Section: Control Of Airway Inflammationmentioning
confidence: 99%
“…One of the most widely used drugs is fluticasone propionate (FP), which also is recommended for the management of recurrent airway obstruction (RAO) and inflammatory airway disease in horses. In RAO‐affected horses, FP (2 mg twice daily for 3 weeks) improves lung function, and a similar dose administered for 2 weeks enhances the improvement in lung function caused by environmental management alone 2,3 . There are no published papers either on the shorter‐term effects of FP in RAO‐affected horses or on the effectiveness of FP for prevention of exacerbations of RAO.…”
mentioning
confidence: 99%